Surgical and Nonsurgical Management of the Nasal Skin-Soft Tissue Envelope - Saadoun, Rakan; Riedel, Frank; D'Souza, Alwyn; Veit, Johannes A. (Facial Plastic Surgery, 2021)
Management of the skin-soft tissue envelope (SSTE) in rhinoplasty is challenging and critical for the overall outcome. The preoperative identification of patients with thick or thin skin and with preexisting skin conditions may contribute significantly to the postsurgical result. Most publications and textbooks focus on the management of the osseocartilaginous framework, but the SSTE management is often not addressed in detail. However, nonsurgical treatments, such as skin preconditioning, topical steroid-injections, oral isotretinoin, and topical vitamin A derivatives, may provide strong benefits. In this article, we reviewed the literature to present a comprehensive review on the available surgical and nonsurgical approaches pre-, intra-, and postoperatively dealing with SSTE in rhinoplasty.
Keywords: rhinoplasty; nasal skin; skin-soft tissue envelope; thin skin; thick skin; isotretinoin; nonsurgical management